(3QGjGJ GdeHQRjf hZGjGJ GdeejRjfs - (3Ydj Hf ehSi Hf eMeO Hf YHO Gdedc GHf SYjO, GdYfSj GdeOdLj GdeZQHj , CHh GdMSf, fhQ GdOjf,J (B685 (3g` s ((3jhSa Hf eMeO hYQa HGHf Gdhcjd Gdejdhi s)
(3ChdgG (B:s
(3MeO Gddg Chdi eG jbOe s
(3BNQgG (B:s
(3bGd GdeDda hcGf JcedjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B249s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B142 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs